Probing the drug delivery strategies in ischemic stroke therapy - Qiong Wu; Rong Yan; Jingjing Sun (Taylor & Francis Group, 2020)
Ischemic stroke, which is caused by a sudden clot in the blood vessels, may cause severe brain tissue damage and has become a leading cause of death globally. Currently, thrombolysis is the gold standard primary treatment of ischemic stroke in clinics. However, the short therapeutic window of opportunity limits thrombolysis utility. Secondary cerebral damage caused by stroke is also an urgent problem. In this review, we discuss the present methods of treating ischemic stroke in clinics and their limitations. Various new drug delivery strategies targeting ischemic stroke lesions have also been summarized, including pharmaceutical methods, diagnostic approaches and other routes. These strategies could change the pharmacokinetic behavior, improve targeted delivery or minimize side effects. A better understanding of the novel approaches utilized to facilitate drug delivery in ischemic stroke would improve outcomes.